The Understanding, Practice, and Implications Spiritual Capital in Disaster Recovery: A Study on Tsunami's Survivors in Sumberjaya, Pandeglang, Banten, Indonesia - Novia Nurul Badi’ah; Ety Rahayu; Isbandi Rukminto Adi (Budapest International Research and Critics University, 2022)
This study aims to reveal the value of spiritual capital in the recovery phase for tsunami survivors in Sumberjaya, Pandeglang, Banten, Indonesia. The research location was chosen because it is prone to tsunamis and earthquakes. Moreover, the survivors living in refugee camps faced double disasters, the post-Pandeglang tsunami in 2018 and Covid-19 in early 2020, while still living in temporary shelter locations that year. This study uses a qualitative method with a case study approach. The data collection technique used in-depth interviews, documentation, and literature study. The novelty of this research is to raise the issue of post-disaster spiritual capital in Pandeglang, which is still rarely discussed. This study concludes that there is an understanding that economic recovery and mental recovery are essential for citizens, the existence of antecedent values and humility shape the willingness and desire to recover, and forgetting the past is a turning point to recover from previous good memories of a tsunami.